The specialising or sampling debate: a retrospective analysis of adolescent sports participation in the UK - Bridge, M. W.; Toms, M. R. (Journal of Sports Sciences, 2013)
Whether young people should specialise in one competitive sport at an early age, or pursue a wider range of sports during adolescence is a topic of some debate (Baker, Cobley, & Fraser-Thomas, 2009) and is fundamental within sports policy and coaching practice. The purpose of this retrospective recall study was to identify whether early specialisation or sporting diversification (sampling) throughout childhood and adolescence can influence performance levels prior to adulthood. An online questionnaire was used to collect the sport participation histories of 1006 UK sports people, which were then compared with the developmental framework provided by the Developmental Model of Sport Participation (DMSP, Côté & Fraser-Thomas, 2007). A significant association between the number of sports participated in at the ages of 11, 13, and 15 and the standard of competition between 16 and 18 years was found. Individuals who competed in three sports aged 11, 13, and 15 were significantly more likely to compete at a national compared with club standard between the ages of 16 and 18 than those who practised only one sport. The findings reported here provide some empirical support for the sampling performance pathway DMSP model in a UK context.